Efek Virgin Coconut Oil (VCO) Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Rahmiati Rahmiati (Herbal Medicine Journal, 2020)
Staphylococcus aureus is one of the bacteria that causes pyogenic infections of the skin. Infections caused by Staphylococcus aureus include boils, pimples, and wound infections. Virgin Coconut Oil (VCO) is genuine coconut oil made from fresh coconut raw materials and operates with control and without chemicals. The results of the coconut oil management process can produce essential compounds containing lauric acid, so that pure coconut oil has anti-bacterial properties. The purpose of this study was to see the effect of Virgin Coconut Oil on the growth of Staphylococcus aureus bacteria and to see the potential of Virgin Cococnut Oil as an antibacterial, especially for skin infections. The research method used the dick disc method with various concentrations consisting of 6.25%, 25%, 50%, 75%, 100%. The results showed that VCO had an effect on the growth of Staphylococcus aureus bacteria at a concentration of 100% with an inhibition zone diameter of 10.40 mm in the strong category.